Effect of biologically active additives based on the homogenate of drone larvae on microcirculation and metabolism in Nordic skiers - F. B. Litvin; T. M. Bruk; P. A. Terekhov; I. A. Prokhoda; D. B. Nikityuk; S. V. Klochkova (National Electronic Information Consortium (NEICON), 2020)
Objective: to study the effect of biologically active additives (BAA) based on the homogenate of drone larvae on microcirculation and metabolism in Nordic skiers. Materials and methods: 58 male skiers at the age of 18-20 years ranging from 1 category to CMS were divided into two groups: the main group (30 athletes) and the comparison group (28 athletes). The skiers of the main group used the homogenate of drone larvae daily at a dose of 10 mg/kg of body weight during 21 days. Athletes from the comparison group received potato starch (placebo). The study of the microcirculation system was performed with a laser analyzer of the capillary blood flow «LAKK-M» before the BAA administration, at the 1st, 10th and 21st days of the study and 30 days after the end of the BAA administration. Results: A significant increase in perfusion was observed in the experimental group (121%, p